Project Based Learning: Enhancing Character and Creative Thinking Skills through Activity-Based Projects in Numeracy Literacy Courses - Rediani, Ni Nyoman; Palittin , Ivylentine Datu; Kaize, Bernadetha Rizki (Universitas Pendidikan Ganesha, 2024)
The numerous incidents of fights and bullying among students indicate current problems with character development. Additionally, advances in technology and science require individuals to master creative thinking skills. Therefore, this study aims to explore the impact of an activity-based PjBL model on the development of character and creative thinking skills. This research employs a quasi-experimental design known as the nonequivalent post-test only control group design. The population consists of all elementary education students enrolled in the Numeracy Literacy Development course, totaling 120 students. Tests and questionnaires are often used in research to collect data. The data collection methods employed in this study involve descriptive analysis and inferential statistical analysis. Inferential analysis was conducted using MANOVA. The research results indicate differences in character and creative thinking skills after students were taught using the Activity-Based PjBL Model. Based on the study, there are differences in character and creative thinking skills, as seen from the differences in mean values. The difference in character between students taught with the Activity-Based PjBL model and those who were not was 13.74, with the experimental group having a higher average character. Similarly, the difference in creative thinking skills between students taught with the Activity-Based PjBL model and those who were not was 11.44, with the experimental group showing a higher average creative thinking ability. Additionally, the analysis indicates that the variable influencing more is character rather than creative thinking skills. These findings provide a strong basis for recommending the activity-based PjBL model as a solution to improve students' character and creative thinking skills. This model not only focuses on the completion of concrete projects but also integrates activities that encourage collaboration, problem-solving, and innovation.